Protective effects of exogenous and endogenous hydrogen sulfide in mast cell-mediated pruritus and cutaneous acute inflammation in mice. (January 2017) - Rodrigues, L.; Ekundi-Valentim, E.; Florenzano, J.; Cerqueira, A.R.A.; Soares, A.G.; Schmidt, T.P.; Santos, K.T.; Teixeira, S.A.; Ribela, M.T.C.P.; Rodrigues, S.F.; de Carvalho, M.H.; De Nucci, G.; et al.
Graphical abstract: Abstract: The recently described 'gasomediator' hydrogen sulfide (H2 S) has been involved in pain mechanisms, but its effect on pruritus, a sensory modality that similarly to pain acts as a protective mechanism, is poorly known and controversial. The effects of the slow-releasing (GYY4137) and spontaneous H2 S donors (Na2 S and Lawesson's reagent, LR) were evaluated in histamine and compound 48/80 (C48/80)-dependent dorsal skin pruritus and inflammation in male BALB/c mice. Animals were intradermally (i.d.) injected with C48/80 (3 μg/site) or histamine (1 μmol/site) alone or co-injected with Na2 S, LR or GYY4137 (within the 0.3–100 nmol range). The involvement of endogenous H2 S and KATP channel-dependent mechanism were also evaluated. Pruritus was assessed by the number of scratching bouts, whilst skin inflammation was evaluated by the extravascular accumulation of intravenously injected 125 I-albumin (plasma extravasation) and myeloperoxidase (MPO) activity (neutrophil recruitment). Histamine or C48/80 significantly evoked itching behavior paralleled by plasma extravasation and increased MPO activity. Na2 S and LR significantly ameliorated histamine or C48/80-induced pruritus and inflammation, although these effects were less pronounced or absent with GYY4137. Inhibition of endogenous H2 S synthesis increased both Tyrode and C48/80-induced responses in the skin, whereas the blockade of KATP channels by glibenclamide did not. H2 S-releasing donors significantly attenuate C48/80-induced mast cell degranulation either in vivo or in vitro . We provide first evidences that H2 S donors confer protective effect against histamine-mediated acute pruritus and cutaneous inflammation. These effects can be mediated, at least in part, by stabilizing mast cells, known to contain multiple mediators and to be primary initiators of allergic processes, thus making of H2 S donors a potential alternative/complementary therapy for treating inflammatory allergic skin diseases and related pruritus.